PENGARUH TOTAL ASSET TURN OVER DAN NET PROFIT MARGIN TERHADAP RETURN ON ASSET PADA PT NIPPON INDOSARI CORPINDO TBK PERIODE 2012-2021 - Rita Satria; Imaula Zuhriyah Agustina; Elva Herlianti (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study aims to determine the effect of Total Asset Turnover and Net Profit on Return on Assets at PT Nippon Indosari Corpindo Tbk for the 2012-2021 period partially or simultaneously. The selection of independent variables used in this study is Total Asset Turnover and Net Profit Margin. While the dependent variable is Return on Assets (ROA). The population in this study is the annual financial statements of PT Nippon Indosari Corpindo Tbk which are listed on the Indonesia Stock Exchange (IDX). Meanwhile, the samples used in this study are all balance sheets and income statements at PT Nippon Indosari Corpindo Tbk for the 2012-2021 period. The sample selection was carried out using purposive sampling, namely by collecting, recording and reviewing secondary data in the form of the company's financial statements. The analytical method uses descriptive statistical analysis, classical assumption test, t test, f test and coefficient of determination test (R2) using SPSS 25 application. The results of this study indicate that partially Total Asset Turnover and Net Profit Margin have a significant effect on Return on Assets. Simultaneously Total Asset Turnover and Net Profit Margin have a significant effect on Return on Assets.